Clinical and socioeconomic factors associated with unrecognized peripheral artery disease. (August 2014) - Chang, Peter; Nead, Kevin T; Olin, Jeffrey W; Cooke, John P; Leeper, Nicholas J
Peripheral artery disease (PAD) is a highly prevalent condition that frequently goes undetected and untreated. Socioeconomic factors associated with unrecognized PAD are not known. The ankle–brachial index (ABI) was calculated in 1656 study participants undergoing non-emergent coronary angiography with PAD defined as an ABI <0.9. Subjects were followed for mortality and cardiovascular outcomes. Compared to those without PAD, those with unrecognized PAD at enrollment were older, had higher rates of cardiovascular comorbidities, and had higher major adverse cardiovascular events (MACE) ( p <0.03 for all). Among those enrolling without a reported history of PAD, there was a higher prevalence of PAD with decreasing income ( p =0.004), education level ( p <0.001), social isolation ( p =0.027) and depression ( p =0.034); 50% of these individuals reported symptoms suggestive of claudication. In conclusion, the prevalence of unrecognized PAD is high amongst a cohort of high-risk individuals referred for coronary angiography. A profile of lower socioeconomic status is associated with unrecognized PAD. These subjects will report symptoms suggestive of claudication and impaired walking ability when directly queried.